Early Cenozoic activated deformation in the Qilian Shan, northeastern Tibetan Plateau: Insights from detrital apatite fission‐track analysis. (7th February 2021) - He, Pengju; Song, Chunhui; Wang, Yadong; Wang, Daichun; Chen, Lihao; Meng, Qingquan; Fang, Xiaomin
Abstract: The evolution of the tectonic deformation of the northeastern Tibetan Plateau (TP) in the Cenozoic is significant for understanding plateau growth during India‐Asia convergence. However, when deformation began and how it has developed in this pivotal region remain controversial. We focus on the temporal progress of Cenozoic deformation in the Qilian Shan, a major tectonic belt of the northeastern TP. In the present study, detrital apatite fission‐track (AFT) thermochronological analysis was performed on Oligocene‐Quaternary synorogenic sediments in the northern Qaidam Basin, where detritus is sourced from the Qilian Shan. Age components of buried but unannealed detrital AFT samples reveal two static peaks (i.e., peak ages that are consistent upsection) at ca. 60–50 Ma and ca. 40–36 Ma and a moving peak (i.e., peak ages that are younger upsection) with increased lag time during ca. 30–8 Ma. These new detrital AFT ages, integrated with the analysis of sedimentary provenance and data from previously published studies, indicate that Cenozoic tectonic deformation began in the Qilian Shan in the late Paleocene‐early Eocene. Furthermore, the Qilian Shan experienced a subsequent episodic deformation event in the late Eocene and the deformation or erosion of some terranes in the Qilian Shan decelerated during the Oligocene‐Miocene. Our results suggest that the northeastern TP responded to the India‐Asia collision almost instantaneously. Abstract : Detrital apatite fission track analysis on synorogenic sediments in the northern Qaidam Basin indicate that Cenozoic tectonic deformation began in the Qilian Shan in the late Paleocene‐early Eocene.